2021
DOI: 10.3389/fspas.2021.741053
|View full text |Cite
|
Sign up to set email alerts
|

The Capability of Utilizing Abiotic Enantiomers of Amino Acids by Halomonas sp. LMO_D1 Derived From the Mariana Trench

Abstract: D-amino acids (D-AAs) have been produced both in organisms and in environments via biotic or abiotic processes. However, the existence of these organic materials and associated microbial degradation activity has not been previously investigated in subduction zones where tectonic activities result in the release of hydrothermal organic matter. Here, we isolated the bacterium Halomonas sp. LMO_D1 from a sample obtained from the Mariana trench, and we determined that this isolate utilized 13 different D-AAs (D-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…D-AAs are among the most important components of RDOM, which are widely present in the deep sea and has a higher concentration in marine sediments than in seawater ( 14 ). At present, a variety of deep-sea microorganisms that can utilize D-AAs have been isolated ( 18 , 20 ), and the bioavailability of D-AAs in the deep ocean has been shown to be equal to or even higher than that of L-AAs ( 20 , 40 ); thus, D-AAs are an important source of nutrients for benthic microbes. In this study, we found that the deep-sea sediment-derived Shewanella strain WP2 can utilize D-Glu, D-Ala, and D-Ser as a single nitrogen source for growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…D-AAs are among the most important components of RDOM, which are widely present in the deep sea and has a higher concentration in marine sediments than in seawater ( 14 ). At present, a variety of deep-sea microorganisms that can utilize D-AAs have been isolated ( 18 , 20 ), and the bioavailability of D-AAs in the deep ocean has been shown to be equal to or even higher than that of L-AAs ( 20 , 40 ); thus, D-AAs are an important source of nutrients for benthic microbes. In this study, we found that the deep-sea sediment-derived Shewanella strain WP2 can utilize D-Glu, D-Ala, and D-Ser as a single nitrogen source for growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although D-AAs are normally considered RDOM, they can be utilized by some microorganisms as nutrient sources ( 4 , 15 ). Recently, many D-AA-utilizing microorganisms have been found in diverse habitats, including soils, limnological waters, marine sediments, and seawater ( 16 18 ). For samples from the surface seawater and sediments (depth <356 m) of Kongsfjorden, bacterial strains belonging to 12 families and 3 phyla were enriched in culture with D-AAs as the sole nitrogen source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, for D-amino acid (D-AA) metabolism, the catabolic capacities for nine D-AAs, including two typical D-AAs in bacterial cell walls (i.e., D-Ala, D-Glu) and seven non-canonical D-AAs (i.e., D-Gln, D-Ser, D-Thr, D-Arg, D-Pro, D-Phe and D-Cys), were found in MAGs from both ME and MT. Among them, dadA, the typical gene for a broad-spectrum D-AA dehydrogenase in D-AA catabolism [62], was abundant and found in 445 (of 1176) MAGs (59% in ME and 35% in MT). Almost all identified class-level clades (81/84) contain at least one D-AA metabolic gene(s) (Fig.…”
Section: Degradationmentioning
confidence: 99%